Replacing actual political activism with ethical shopping: The case of Oatly. (April 2020) - Ledin, Per; Machin, David
Abstract: There has been an increase of food products marketed through buzzwords like organic, 'local', 'recyclable', 'Fair-trade'. These have been described as part of a newer kind of ethical or emotional capitalism, where consumers can align with political issues through acts of shopping. The problem is that such acts replace or shape what we know about, and how we act towards, actual socio-political matters. In this paper, we look at one example of such a product: Oatly, a milk alternative, which brands itself as sustainable and anti-corporate. Taking a Multimodal Critical Discourse Analytical approach, we want to learn more about how such brands do not actually state details of the socio-political issue alongside which they align (its causes, process, solutions) yet successfully communicate a compelling sense that buying the product is a form of social activism in a way which cleverly implicates consumers to internalize its values and give them a powerful sense of being part of a political moral order. And this is a form of activism which is fun, chic and rather easy.